ANALISA PENGARUH PERSENTASE REDUKSI TERHADAP STRUKTUR MIKRO DAN SIFAT MEKANIK PENARIKAN KAWAT BAJA AISI 1006 - Fauziah, Febby; Muliastri, Destri; Muhammad, Wildan (Politeknik Negeri Sriwijaya, Indonesia, 2024)
The wire drawing process is a metal forming process by pulling the wire bar through the dies by a tensile force. The purpose of this process is to reduce the diameter of the wire rod without reducing volume and mass. The material used in this study was AISI 1006. The percentage of reduction is 22.14%, 17.35%, and 14.26%. The microhardness of these wires was tested using Microhardness Vickers Method, the result is 37.6433 HV, 37.7666 HV, and 38.6233 HV respectively. The maximum tensile strength value of the wires is 197.8146 MPa, 111.271 MPa, and 71.005 MPa, while the yield strength is found to be 176.379 MPa, 100.926 MPa, and 64.593 MPa. With a greater percentage of reduction on the wire, the microstructure became elongated, flatter, and much denser. Â